P801 Physicians' knowledge and application of immunisation strategies in patients with inflammatory bowel disease: a survey by the Italian Group for the study of inflammatory bowel disease (IG-IBD). (25th January 2019) - Macaluso, F S; Mazzola, G; Ventimiglia, M; Alvisi, P; Renna, S; Adamoli, L; Galli, M; Armuzzi, A; Ardizzone, S; Cascio, A; Cottone, M; Orlando, A
Abstract: Background: No data on European countries about knowledge and application of immunisation strategies in patients with inflammatory bowel disease (IBD) are available. We designed a questionnaire aimed at exploring these issues among Italian gastroenterologists dealing with adult and paediatric IBD. Methods: An anonymous, 24-item, questionnaire was sent via e-mail to all members of the Italian Group for the study of inflammatory bowel disease (IG-IBD). Three sets of questions were formulated: 1. Characteristics of respondents; 2: General opinions on the role of vaccines in IBD patients; 3: Immunisations of IBD patients in clinical practice. Results: Of the 455 total surveys sent, there were 198 respondents (response rate: 43.5%). The great majority of respondents (82.9%) reputed as 'very important' to perform the vaccinations recommended by the guidelines in patients with IBD. Data on vaccines status of IBD patients are 'always' collected by 23.3% of the respondents and 'most of the times' by 63.9% of them, while the indication to perform the vaccinations recommended by the guidelines is 'always' given by 55.9% of the surveyed IG-IBD members. The indication to immunisation is given at the diagnosis of the disease by 55.6% of the respondents. The most frequently recommended vaccine in IBD patients is the annual flu vaccine, while the recommendation rates for the other vaccines is variable depending on the different pathogens. Conclusions: Efforts carried out by the scientific societies are required to increase the awareness of this relevant topic among physicians.